A conceptualization of suppliers' and buyers' abilities in product development: Cases from the retail industry. Issue 3 (10th August 2018) - Bjerhammar, Lena; Elbe, Jörgen
Abstract : Purpose: The purpose of this paper is to present a conceptual framework of specified buyer and supplier abilities which may be apparent in processes when firms wish to develop products where other features than function are important. Design/methodology/approach: Data were collected through personal interviews with managers at eight major Swedish retail chains. The framework has been developed from an analysis of the data. Three of the cases are presented to illustrate how the framework may be applied. Findings: The framework contains the concepts specification ability and description ability, which define and specify the demand abilities of the buyer, and the concepts translation ability, interpretation ability and implementation ability, which define and specify the problem-solving abilities of the supplier. Originality/value: The framework presented here contributes to the business relationship and network literature on product development processes by highlighting and conceptualizing the process between buying firms who have different abilities or even inabilities to specify and explain desired product qualities, and the suppliers who should interpret the demands of these buyers.